EIL IN PRACTICE: INDONESIAN AND CHINESE INTERNATIONAL POSTGRADUATE STUDENTS NEGOTIATE MEANING - Umar Abdullah (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
Interaction in English as an International Language (EIL) setting provides myriad opportunities for negotiation of meaning, arguably beneficial for language acquisition. The present study aims at finding out how meaning is negotiated in EIL interaction among two groups of postgraduate TESOL international students from two Asian countries, Indonesia and Peopleâs Republic of China (PR China). The findings reveal that the students indeed utilized various strategies such as clarification requests, confirmation checks, comprehension checks, word-coinage, and use of approximation, self-repetition, other repetition, self-correction, and non-verbal expression of non-understanding. The relative frequency of strategies used appears to have been influenced by the interaction tasks. The variation of strategies across the three pairs is relatively similar. Some EIL features corresponding to pronunciation and grammatical structures also emerge in the present study. Finally, the study suggests that negotiation strategies need to be included in the English teaching syllabus. Moreover, current foreign or second language teaching methodology needs to pay serious attention to EIL features and to develop learnersâ intelligibility and communication strategies by making them aware of standard varieties of English.Â